2008
DOI: 10.1037/0021-9010.93.5.945
|View full text |Cite
|
Sign up to set email alerts
|

Affective mechanisms linking dysfunctional behavior to performance in work teams: A moderated mediation study.

Abstract: The present study examines the association between dysfunctional team behavior and team performance. Data included measures of teams' dysfunctional behavior and negative affective tone as well as supervisors' ratings of teams' (nonverbal) negative emotional expressivity and performance. Utilizing a field sample of 61 work teams, the authors tested the proposed relationships with robust data analytic techniques. Results were consistent with the hypothesized conceptual scheme, in that negative team affective ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
260
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(282 citation statements)
references
References 113 publications
9
260
1
5
Order By: Relevance
“…This mechanism is consistent with the "spillover effect," which suggests that individuals become more mentally accessible when they observe their teammates acting in certain ways [23,24]. In previous studies of workgroup aggression, the spillover effect has been described as "contagious aggression," in which instigators set off team members one after another [13,25,26].…”
Section: The Emergence Of Team Incivility Climatesupporting
confidence: 64%
See 3 more Smart Citations
“…This mechanism is consistent with the "spillover effect," which suggests that individuals become more mentally accessible when they observe their teammates acting in certain ways [23,24]. In previous studies of workgroup aggression, the spillover effect has been described as "contagious aggression," in which instigators set off team members one after another [13,25,26].…”
Section: The Emergence Of Team Incivility Climatesupporting
confidence: 64%
“…Team settings intensify the emergence of incivility even further, as shown in a study that examined dysfunctional behaviors at the team level [13]. Social learning theory [22] proposes that individuals model each other's actions after observing their behaviors.…”
Section: The Emergence Of Team Incivility Climatementioning
confidence: 99%
See 2 more Smart Citations
“…To investigate this possibility, we estimated an alternative path analytic model with venture growth as the antecedent and focus on opportunities as the outcome variable (the other variables in the model were identical). Researchers have suggested that testing such reversed causal models may provide preliminary evidence for the direction of causality (e.g., Cole, Walter, & Bruch, 2008). Results showed that the fit of this alternative model was significantly worse (Satorra-Bentler adjusted χ2 (42) = 45.63) than our hypothesized model (Satorra-Bentler adjusted χ2 (42) = 7.15; χ2 difference to alternative model = 38.48; p < .01).…”
Section: Post-hoc Analyses To Oppose Alternative Explanationsmentioning
confidence: 72%